Implementation of the Waste Bank Program in Instilling Islamic Ecotheology Values - Wahyu Padila; Mahariah Mahariah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the implementation of the Waste Bank Program in instilling Islamic ecotheology values at MAN 2 Deli Serdang using a qualitative case study approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model and tested for validity through source and technique triangulation. The results of the study indicate that the Waste Bank Program not only functions as an environmental management activity but also as a medium for internalizing Islamic ecotheology values, such as cleanliness as part of faith, trustworthiness, mīzān (balance), and the prohibition of fasād (destruction). The internalization of values occurs gradually through habituation, teacher role modeling, and integration into madrasah activities and culture.  In addition, changes in student behavior were found in maintaining cleanliness and reducing the use of single-use plastics, although they are still situational and dependent on supervision. This program is supported by the commitment of the madrasah, the role of teachers, adequate facilities, as well as student participation, but there are still obstacles in the form of inconsistent behavior and the suboptimal internalization of values.